(untitled) (Palimpsesto, 2017)
In the periphery of the Spanish empire, a poor territory with an unsubmissive indigenous frontier, the building of Chile’s colonial society was structured along a series of assumptions and realities, among which war and consequently the omnipresence of a military spirit were noteworthy. This factor would be trascendental for the configuration of local elites in terms of its prestige and its aristocratic imagery. In addition, the steps through which it was customary to ascend to the pinnacle of the peripheral “nobility” of Santiago de Chile included landownership, encomiendas — both substantial ingredients of the imagery of and support for neo-feudal culture in Hispanic American colonies — appointments to public office within the State apparatus and the municipal Cabildo. In this context we’ll explore scenarios, pretensions, decisions and accomplishments that sowed the life trajectories of three people that headed consecutive generations of the Erazo family in the span of a century.